Modern Materials and Technologies for Civil and Road Engineering - Putra Jaya, Ramadhansyah (Trans Tech Publications Ltd, 2021)
Selected, peer-reviewed papers from the 4th National Conference on Wind and Earthquake Engineering (4th NCWE), October 16-17, 2020, Gambang, Malaysia